PROFIL STATUS GIZI ATLET KEMPO SULAWESI UTARA - Christoforus Manopo; Mokoagow Mokoagow; Bokau Bokau (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
This research aims to determine the nutritional status profile of Kempo athletes in North Sulawesi. Nutritional status is an important factor in supporting athletic performance, especially in the sport of Kempo, which requires strength, speed, and endurance. This research uses a descriptive method with a quantitative approach to measure the nutritional status of athletes through Body Mass Index. (IMT). The research sample consists of 40 Kempo athletes in North Sulawesi aged 17 and above. The research results show that the majority of athletes have an ideal nutritional status, with 95% of the total sample falling into the normal weight category, while the remaining 5% are classified as having mild underweight. This finding shows that Kempo athletes in North Sulawesi generally have good nutritional status and are ready to compete in matches with optimal physical condition. This research is expected to raise awareness of the importance of balanced nutrition for athletes to support optimal performance in sports.